Consumer Perceptions of Lean and Green Manufacturing Practices and Their Impact on Sustainability Performance in Coffee Chains - Winda Padilah; Kuncorosidi Kuncorosidi (STIESA Press, 2025)
Coffee consumption has become an important part of social and economic culture in many countries. The global chain of coffee shops has grown rapidly, becoming an exciting phenomenon in the coffee industry. However, with this growth, the coffee industry faces sustainability challenges. This study aims to examine how Lean and Green Manufacturing practices affect the impact of Sustainability Performance on Fore Coffee. This study uses a quantitative method by collecting data through a questionnaire distributed to 100 consumers who have consumed Fore Coffee. Data analysis was carried out using multiple linear regression techniques to evaluate the relationships between the variables studied. Research shows that Lean Manufacturing and Green Manufacturing have a significant influence on Sustainability Performance at Fore Coffee. Multiple linear regression analysis indicates that these two variables play an important role in improving a company's sustainability performance. These results highlight the importance for companies to focus on implementing efficient and environmentally friendly manufacturing strategies to support improved sustainability performance.